Analisi Quality of Service Pada Routing EIGRP Berbasis Algoritma Distance Vector - Sundari, Siti; Damayanti, Fera; Marwan, Andi (Journal Global Technology Computer, 2024)
In computer networks, routing protocols play an important role in determining the best path to send data packets. Enhanced Interior Gateway Routing Protocol (EIGRP) is a routing protocol based on the Distance Vector algorithm that is widely used because of its ability to quickly converge and efficiently use network resources. However, the problems faced by EIGRP performance in various network scenarios, such as topology changes and traffic density, are still challenges that need further analysis. Therefore, this research aims to analyze the Quality of Service (QoS) in EIGRP routing based on main parameters such as delay, throughput, packet loss and jitter. The method used in this research involves network simulation using simulation software, where scenarios with various variations in network topology and load are tested to evaluate EIGRP performance. The main contribution of this research is to provide deeper insight into the effectiveness of EIGRP in supporting optimal Quality of Service in various network conditions. Interim results show that EIGRP is able to provide stable performance in networks with minimal topology changes, but experiences increased delay and packet loss in high traffic conditions. It is hoped that this research can be a reference for network administrators in optimizing the use of EIGRP to support better network performance.